2019
DOI: 10.12973/ijem.5.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Child-Friendly Schools: An Assessment of Kindergartens

Abstract: Child Friendly School (CFS) is a democratic environment based on children's rights, where all students are accepted, teaching-learning processes are organized according to children's interest needs, health, safety and protective measures are taken for children and gender-based discrimination is not provided. Preschool education institutions, which are considered to be very effective on the future of the child and the society, should be child friendly in this way. The aim of this study is to identify the teachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
0
12
0
3
Order By: Relevance
“…Teacher knowledge on the curriculum (KEC) supports the abilities of teachers to provide a learning environment according to the context or stage of children's development, and all of these are factors affecting early childhood learning (Inan, 2010). The result of another study that supports the importance of knowledge about learning strategies is revealed by Cobanoglu & Sevim (2019) that children must feel comfortable with learning in a school environment.…”
Section: Discussionmentioning
confidence: 83%
“…Teacher knowledge on the curriculum (KEC) supports the abilities of teachers to provide a learning environment according to the context or stage of children's development, and all of these are factors affecting early childhood learning (Inan, 2010). The result of another study that supports the importance of knowledge about learning strategies is revealed by Cobanoglu & Sevim (2019) that children must feel comfortable with learning in a school environment.…”
Section: Discussionmentioning
confidence: 83%
“…Safe learning environments provide adequate toilet facilities, garbage disposal, and handwashing in classrooms or in centers' common spaces (Cobanoglu and Sevim 2019). For example, in Mindanao, the Philippines, ECE centers and primary schools purchased cost-effective, sturdy 500-gallon plastic water tanks, rainwater catchment devices, rubber pipes, and washbasins.…”
Section: Principles Of Quality Early Learning Environments In Ece Ove...mentioning
confidence: 99%
“…Security protocols to manage emergencies (earthquakes, floods, fire, and the like) and universal access to safe spaces are necessary for overall safety (Britto 2017;Duarte, Jaureguiberry, and Racimo 2017). ECE centers and schools should provide educators and children with the necessary places and instructions to minimize hazardous environments (Cobanoglu and Sevim 2019) and to manage the community's safety during emergencies. An interesting low-cost example of evacuation equipment combining safety and child well-being is the Chilean evacuation slide.…”
Section: Principles Of Quality Early Learning Environments In Ece Ove...mentioning
confidence: 99%
“…One of the problems faced by educational institutions that emphasize the importance of developing aspects of life skills is that they still require improvements to the curriculum, teaching facilities, teaching methods, learning media, competent teachers, and evaluation tools (Prasetyo et al, 2021). Developed a culture-based learning model in elementary schools with an orientation to inculcate noble values in accordance with local government policies (Ghufron et al, 2017), without ignoring the national curriculum (Cobanoglu & Sevim, 2019;Suharta & Septiarti, 2018).…”
Section: Introductionmentioning
confidence: 99%